Investigation of Machining Parameter in EDM of High Carbon Steel Alloy (EN31). (2017) - Koteswararao, B.; Siva kishore Babu, K.; Ravi, D.; Kumar, K.Kishore; Chandra shekar, P.
Abstract: The selection of manufacturing conditions is one of the most important aspects to take into consideration in the majority of manufacturing processes, particularly Electrical Discharge Machining (EDM) process. EN31 is high carbon alloy steel and is usually supplied in a hardened and tempered condition. An attempt is made to find out the effect of machining parameters on EN31. Moreover, the signal-to-noise ratios associated with the observed values in the experiments were determined to find which factor is most affected by the Responses of Material Removal Rate (MRR), Tool Wear Rate (TWR) and over cut (OC).Discharge current(I) is most influencing factor on MRR and then pulse duration time and the last is diameter of the tool(D). MRR increased with I. As the pulse duration extended, MRR decreases monotonically. In the case of TWR the most important factor is I then pulse on time and after that D. In the case of OC the most important factor is I and then D and no effect on pulse on time.